Core Competencies in Clinical Neuropsychology as a Training Model in Europe - Kosmidis, Mary H.; Lettner, Sandra; Hokkanen, Laura; Barbosa, Fernando; Persson, Bengt A.; Baker, Gus; Kasten, Erich; Ponchel, Amélie; Mondini, Sara; Varako, Nataliya; Nikolai, Tomas; Jónsdóttir, María K.; et al. (Frontiers in Psychology, 2022)
The multitude of training models and curricula for the specialty of clinical neuropsychology around the world has led to organized activities to develop a framework of core competencies to ensure sufficient expertise among entry-level professionals in the field. The Standing Committee on Clinical Neuropsychology of the European Federation of Psychologists’ Associations is currently working towards developing a specialty certification in clinical neuropsychology to establish a cross-national standard against which to measure levels of equivalency and uniformity in competence and service provision among professionals in the field. Through structured interviews with experts from 28 European countries, we explored potential areas of core competency. Specifically, questions pertained to the perceived importance of a series of foundational, functional, and other competencies, as well as current training standards and practices, and optimal standards. Our findings revealed considerable agreement (about three quarters and above) on academic and clinical training, despite varied actual training requirements currently, with fewer respondents relegating importance to training in teaching, supervision, and research (a little over half), and even fewer to skills related to management, administration, and advocacy (fewer than half). European expert clinical neuropsychologists were in agreement with previous studies (including those conducted in the U.S., Australia, and other countries) regarding the importance of sound theoretical and clinical training but management, administrative, and advocacy skills were not central to their perspective of a competent specialist in clinical neuropsychology. Establishing a specialty certificate in clinical neuropsychology based on core competencies may enable mobility of clinical neuropsychologists across Europe, and, perhaps, provide an impetus for countries with limited criteria to reconsider their training requirements and harmonize their standards with others.